Loss of heterozygosity analysis at the BRCA loci in tumor samples from patients with familial breast cancer - Ana Osório; Miguel de la Hoya; Raquel Rodríguez‐López; Ángel Martínez‐Ramírez; Alicia Cazorla; Juan José Granizo; Manel Esteller; Carmen Rivas; Trinidad Caldés; Javier Benı́tez (2002)
The BRCA1 and BRCA2 genes are responsible for a high proportion of familial breast cancer; germline mutations in these genes confer a lifetime risk of about 70% for developing breast cancer. Most of the described deleterious mutations are small deletions or insertions that originate a truncated protein; however, in many cases, they are amino acid changes whose significance is unknown. In these cases, there are some tests that can analyze the meaning of these variants, but most remain unclassified. The BRCA genes are tumor suppressors and it is believed that complete loss of the wild-type allele is a common mechanism of inactivation in tumors from patients carrying a germline deleterious mutation in these genes; if this is true, loss of heterozygosity (LOH) analysis in the tumor sample could help to distinguish if a rare variant is either a deleterious mutation or a common polymorphism. In the present study, we performed LOH analysis at the BRCA loci in 47 tumors from patients who belonged to high-risk breast cancer families and were carriers of any type of alteration in these genes. Our results suggest that (i) loss of the wild-type allele is the most common mechanism of inactivation in tumors from patients who carry a deleterious mutation in any of the genes, (ii) this loss is not common when we analyze familial tumors not associated with mutations in BRCA and (iii) LOH can be used to clarify variants of unknown significance in the BRCA genes.